2017
DOI: 10.2355/isijinternational.isijint-2016-196
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Liquid/liquid and Gas/liquid Mass Transfers in a Top/Bottom Blowing Converter

Abstract: In this study, a calculation procedure of gas/liquid mass transfer capacity coefficients based on liquid/ liquid ones was developed and cold model studies on benzoic acid transfer between water and liquid paraffin, and oxygen transfer among water, liquid paraffin and air was carried out under various top/bottom blowing rates and liquid/liquid volume ratios. The liquid/liquid mass transfer rate increased with the increase in a top blowing rate, but the increasing rate of a larger vessel diameter to the top blow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A moderate increase of bottom gas flowrate was believed to reduce the mixing time and strengthen the dynamic conditions in the molten bath. [ 14–16 ] In the reported literatures of Asai et al, [ 17 ] Mazumdar et al, [ 18 ] Neifer et al, [ 19 ] and Sano et al, [ 20 ] the results revealed that there was an obvious linear relationship between the mixing time and one‐third of gas flowrate. However, the investigators found that the mixing time did not decrease infinitely with an increase of bottom gas flowrate, especially when the bottom gas flowrate exceeded the critical value, the mixing performance in the converter bath became worse instead.…”
Section: Introductionmentioning
confidence: 99%
“…A moderate increase of bottom gas flowrate was believed to reduce the mixing time and strengthen the dynamic conditions in the molten bath. [ 14–16 ] In the reported literatures of Asai et al, [ 17 ] Mazumdar et al, [ 18 ] Neifer et al, [ 19 ] and Sano et al, [ 20 ] the results revealed that there was an obvious linear relationship between the mixing time and one‐third of gas flowrate. However, the investigators found that the mixing time did not decrease infinitely with an increase of bottom gas flowrate, especially when the bottom gas flowrate exceeded the critical value, the mixing performance in the converter bath became worse instead.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, numerous experimental investigations have been conducted to study the jet characteristics of the traditional oxygen lance and its influence on the stirring process of the molten bath, with a focus on its impact on smelting performance [7][8][9][10][11] . For instance, Collins et al 12) explored 5 the correlation between the maximum penetration depth and jet impact force in the air-water model, highlighting that maximum penetration depth does not necessarily indicate maximum mixing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are many scholars who also conducted the physical experiments to reveal the influence of bottom tuyeres arrangement on the behaviors of the converter. [13][14][15][16][17][18][19][20] Opinions about how the layout of bottom tuyeres affects the stirring force on the bath are still not unanimous in these literatures. Nevertheless, Lai et al 21) and Yang et al 22) both carried out a water model to investigate the mixing efficiency of the BOF with various bottom tuyeres configurations.…”
Section: Introductionmentioning
confidence: 99%